2021
DOI: 10.3390/nu13092911
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Weight and BMI among UK Adults: A Longitudinal Analysis of Data from the HEBECO Study

Abstract: COVID-19-related restrictions impacted weight and weight-related factors during the initial months of the pandemic. However, longitudinal analyses are scarce. An online, longitudinal study was conducted among self-selected UK adults (n = 1818), involving three surveys (May–June, August–September, November–December 2020), covering anthropometric, sociodemographic, COVID-19-related and behavioural measures. Data were analysed using generalised estimating equations. Self-reported average weight/body mass index (B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 63 publications
0
34
0
4
Order By: Relevance
“…The study design has been previously reported ( 33 ). Briefly, this study is a longitudinal analysis of data from an online study of adults, the HEBECO study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design has been previously reported ( 33 ). Briefly, this study is a longitudinal analysis of data from an online study of adults, the HEBECO study.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of outcome and predictor measures can be found in the Supplementary Materials , and have been previously defined ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…To estimate monthly portion intake frequency, responses for all food item questions were converted into monthly portion frequencies, based on previous research [33]. Assuming a minimum of four weeks per calendar month, an answer of 'A few times per day' was scaled up to 56 portions per month (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The study design has been previously reported [33]. Briefly, this study is a longitudinal analysis of data from an online study of adults, the HEBECO study (https://osf.io/sbgru/).…”
Section: Methodsmentioning
confidence: 99%
“…The confinements by the COVID-19 pandemic have changed lifestyle behaviour and have promoted an obesogenic environment. Weight trajectories during the COVID-19 lockdown have been shown [ 21 , 22 ]. It is expected that the COVID-19 pandemic reinforces the obesity pandemic with long-term consequences on the prevalence of overweight and obesity [ 23 ].…”
Section: The Challenge Obesitymentioning
confidence: 99%